Updating “Sub-hourly water temperature data collected across the Nechako Watershed, 2019–2021” to 2024 and with supplemental sitesZenodo - Justin E. Kokoszka; Dylan Broeke; Finn Calder-Sutt; Mostafa Khorsandi; Maria A. Tavares; Stephen J. Déry (Data in Brief, 2025)
This paper provides an update to a previously published data article [1] and associated dataset [2] describing a fully revised and expanded water temperature dataset for the 47,200 km2 Nechako Watershed of northern British Columbia, Canada. Compared to our prior effort, we expanded the number of measurement sites from 25 in 2021 to 32 in 2024. Both previous and new sites record water temperature in the regulated part of the Nechako Watershed and many of its unregulated tributaries. The updated dataset is fully quality-controlled and homogenized across all sites.This dataset relies on a network of in-situ monitoring stations initiated in 2019 across the Nechako Watershed. To date, 32 stations collect water temperature at 15-min intervals for three lakes, 11 creeks, and 18 river sites. Data collection for all sites is generally year-round, which captures extended periods near or at the freezing mark. The associated metadata reports the station’s condition, any issues, the duration of the collection, and concerns/recommendations for the data analysis. The updated dataset can be used for establishing the impacts of hydrometeorological extreme events on water temperatures [3], hydrothermal modeling for climate change studies [4,5], assessing the efficacy of the Nechako River’s Summer Temperature Management Program [6], and for water quality and aquatic habitat suitability analyses [7,8].